Rational drug design, synthesis and biological evaluation of dihydrofolate reductase inhibitors as antituberculosis agents - Tawari, Nilesh R.; Bag, Seema; Raju, Archana; Lele, Arundhati C.; Bairwa, Ranjeet; Ray, Mukti Kanta; Rajan, M. G. R.; Nawale, Laxman U.; Sarkar, Dhiman; Degani, Mariam S. (Future Medicinal Chemistry, 2015)
Background: A series of 2,4-diamino-s-triazines was designed, with potential for activity against Mycobacterium tuberculosis (Mtb) dihydrofolate reductase enzyme, on the basis of virtual screening results and structure-based drug design. Results: The compounds were evaluated against Mtb (H(37)Rv) and their cytotoxicity was assessed using VERO cell lines. Of particular note, two compounds were found to have the most promising antituberculosis activity (6b minimum inhibitory concentration: 1.76 mu M and 6i minimum inhibitory concentration: 1.57 mu M) along with low cytotoxicity (CC50 : > 300 mu M). The enzyme assay results of these two indicated significant inhibition of Mtb dihydrofolate reductase along with selectivity. Selected derivatives were tested against dormant tubercle bacilli in vivo and ex vivo indicating potential inhibition. Conclusion: This study provides promising antituberculosis dihydrofolate reductase inhibitors that can act as potential leads for further development.

Rottlerin derivatives and other compounds from mallotus philippinensis fruits and their potential antimycobactrial activity - Bhardwaj, Rima; Chinchansure, Ashish A.; Kulkarni, Roshan R.; Arkile, Manisha A.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2015)
The methanolic extract of the fruits of Mallotus philippinensis afforded 13 compounds, 7,11-diketo-lanost-3-ol (1, as acetate), lanosta-8-ene-3β-ol (2, as acetate), pregnenolone (3, as acetate), trans-chalcone (4), kamalachalcone E (5), oleanolic acid (6), gallic acid (7), kaempferol (8), myricetin (9), 1-(5,7-dihydroxy-2,2,6-trimethyl-2 H-1-benzopyran-8-yl)-3-phenyl-2-propen-1-one (10), 4′-hydroxyisorottlerin (11), rottlerin (12), and shikimic acid (13). Compound 1 was isolated as a new natural product and its structure was elucidated by 1D and 2D nuclear magnetic resonance analyses including heteronuclear single quantum correlation, heteronuclear multiple-bond correlation, correlation spectroscopy, and nuclear Overhauser effect spectroscopy experiments. All of the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra. Compounds 11 and 12 exhibited promising inhibitory activity with IC50 values of 0.89 ± 0.33 µg/mL (MIC 2.06 ± 0.41 µg/mL) and 7.59 ± 0.42 µg/mL (MIC 11.56 ± 0.35 µg/mL), respectively.

Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.

Recursive partitioning analysis and anti-tubercular screening of 3-aminopyrazine-2-carbohydrazide derivatives - Miniyar, Pankaj; Mahajan, Anand; Anuse, Dattatray; Kumar, Ashish; Barmade, Mahesh; Sarkar, Dhiman; Arkile, Manisha; Khedkar, Vijay (Letters in Drug Design & Discovery, 2019)
Background: Treating tuberculosis is a challenge due to the development of drug resistance. Hence, it is imperative to develop novel leads having high potency and efficacy to curb drug resistance. Methods: The present research work is focused on microwave-assisted synthesis of novel twenty-six 3-amino-N'-benzylidenepyrazine-2-carbohydrazide derivatives (3a-z), where, lyophilization technique was used for isolation of the major intermediate, 3-aminopyrazin-2-carbohydrazide. All synthesized compounds were subjected for anti-tubercular screening against Mycobacterium tuberculosis H37Ra by using XTT Reduction Menadione Assay (XRMA) protocol. Results: Out of 26 synthesized compounds, four N'-substitutedbenzaldehyde-3-amino-pyrazine-2-carbohydrazide derivatives viz. 3i, 3j 3v and 3z showed significant activity against M. tuberculosis H37Ra. The compounds 3i, 3j, 3v and 3z showed 99, 98, 92 and 87 % inhibition respectively as compared to 94% inhibition shown by the standard drug rifampicin. The MIC and IC50 values were in the range of 24.3-110 and 5.9-20.8 mu g/ml respectively. Conclusion: A classification model called Recursive Partitioning (RP) based on binary Quantitative Structure-Activity Relationship (QSAR) was derived for the establishment of structure-activity relationship (SAR). The predictions derived on the basis of RP model were found to be in agreement with anti-tubercular screening data.
Keywords: 3-aminopyrazine; anti-tubercular activity; Carbohydrazide; lyophilization; QSAR; recursive partitioning

Regio selective synthesis of pyrazole derivatives of 5-chloro-2-methoxy phenyl hydrazide and their biological evaluation - Bavishi, Abhay; Vala, Hardev; Swami, Sagar; Thakrar, Shailesh; Shah, Anamik; Sarkar, Dhiman (Journal of Heterocyclic Chemistry, 2025)
Present study involves synthesis of derivatives of (5-chloro-2-methoxyphenyl) (5-alkyl-3-(substituted) (phenyl/alkyl)-1H-pyrazol-1-yl) methanones. Structural elucidation of the synthesized compounds was depicted by the data of 1H and 13C NMR, IR, and Mass spectral analysis. The newly synthesized compounds 1a-1d and 2a-2i were screened in vitro against Mycobacterium tuberculosis H37Ra using an established XRMA protocol. Among the screened compounds, 2d, 2f, and 2h showed good percent inhibition against the active stage of M. tuberculosis H37Ra 80.77, 55.70, and 79.54, respectively, at 30 mu g/mL of inhibitor concentration. Further in secondary screening, compound 2d exhibited significant antitubercular activity on the active stage of M. tuberculosis H37Ra with IC50 of 0.208 mu g/mL. The synthesized compounds were also screened for antibacterial activity and found no significant activity against Gram-positive Bacteria Bacillus subtitles and Staphylococcus aureus and Gram negative bacteria Pseudomonas aeruginosa and Escherichia coli at 30 mu g/mL, which confirms the specificity of inhibitory activity against M. tuberculosis and more selectively against the active stage. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.
Keywords: 5-chloro-2-methoxy phenyl hydrazide; antibacterial activity; Antitubercular activity; Biological evaluation; H37Ra; hydrazide; Pyrazole